Mapping the Implementation of a Clinical Pharmacist-Driven Antimicrobial Stewardship Programme at a Tertiary Care Centre in South India - Vrinda Nampoothiri; Akkulath Sangita Sudhir; Mariam Varsha Joseph; Zubair Mohamed; Vidya Menon; Esmita Charani; Sanjeev Singh (MDPI AG, 2021)
In many parts of the world, including in India, pharmacist roles in antimicrobial stewardship (AMS) programmes remain unexplored. We describe the evolution and effect of the role of adding clinical pharmacists to a multidisciplinary AMS at a tertiary care teaching hospital in Kerala, India. Through effective leadership, multidisciplinary AMS (February 2016) and antitubercular therapy (ATT) stewardship programmes (June 2017) were established. Clinical pharmacists were introduced as core members of the programmes, responsible for the operational delivery of key stewardship interventions. Pharmacy-led audit and feedback monitored the appropriateness of antimicrobial prescriptions and compliance to AMS/ATT recommendations. Between February 2016 and January 2017, 56% (742/1326) of antimicrobial prescriptions were appropriate, and 54% (318/584) of recommendations showed compliance. By the third year of the AMS, appropriateness increased to 80% (1752/2190), and compliance to the AMS recommendations to 70% (227/325). The appropriateness of ATT prescriptions increased from a baseline of 61% (95/157) in the first year, to 72% (62/86, June 2018-February 2019). The compliance to ATT recommendations increased from 42% (25/60) to 58% (14/24). Such a model can be effective in implementing sustainable change in low- and middle-income countries (LMICs) such as India, where the shortage of infectious disease physicians is a major impediment to the implementation and sustainability of AMS programmes.